Transaction costs and agricultural productivity: implications of isolation for rural poverty in Madagascar - Dorosh, Paul A.; Stifel, David; Minten, Bart (International Food Policy Research Institute, 2003)
This paper examines the mechanisms that transmit isolation into poverty in Madagascar using household survey data combined with a census of administrative communes. Given the importance of agriculture to the rural poor, where nine out of ten poor persons is engaged in farming, we concentrate on isolation manifesting itself in the form of high transaction costs such as the cost of transporting agricultural commodities to major market centers. We find that (a) the incidence of poverty in rural Madagascar increases with remoteness; (b) yields of major staple crops fall considerably as one gets farther away from major markets; (c) and the use of agricultural inputs declines with isolation. Simulation results using output from rice production function estimates suggest that halving travel time per kilometer on major highways (feeder roads) will increase primary season rice production by 1.3 (1.0) percent.